2012
DOI: 10.1097/mao.0b013e318268d1cd
|View full text |Cite
|
Sign up to set email alerts
|

Functional Results and Quality of Life After Retrosigmoid Vestibular Neurectomy in Patients With Ménière’s Disease

Abstract: Retrosigmoid VN is a valuable and safe surgical option to treat disabling MD that has proved resistant to medical treatments. It may also be indicated for patients with preoperative severely impaired thresholds of hearing, in whom a certain hearing gain may be observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
(22 reference statements)
2
10
0
2
Order By: Relevance
“…Overall, the efficacy of RLVNS (i.e., complete resolution of episodic vertigo) in our series was 93%; this is in line with rates reported in the literature 10, 15,17,18 (see ►Table 2). The patients who had imbalance after surgery experienced improvement in their disequilibrium symptoms after completing outpatient vestibular physical therapy.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, the efficacy of RLVNS (i.e., complete resolution of episodic vertigo) in our series was 93%; this is in line with rates reported in the literature 10, 15,17,18 (see ►Table 2). The patients who had imbalance after surgery experienced improvement in their disequilibrium symptoms after completing outpatient vestibular physical therapy.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have reported the hearing loss rate and vertigo control with vestibular nerve section and gentamicin treatment separately. Schlegel et al 6 have demonstrated that the results after VNS proved to be more consistent than those reported after chemical deafferentation of the labyrinth with aminoglycosides. The outcome after chemical labyrinthectomy using aminoglycosides is often satisfactory, but unpleasant ataxia, more intense tinnitus, and a postoperative decrease in hearing are not rare.…”
Section: Labyrinthectomy Versus Intratympanic Aminoglycosidesmentioning
confidence: 75%
“…Schlegel et al 6 have demonstrated 95.5% of hearing function preservation, and on the vestibular side, the medium to long-term evolution of the operated patients showed that durable suppression or significant improvement of the vertigo was achieved in 90.9% of them. According to the literature, ablative surgical deafferentation, such as vestibular neurectomy, remains the most efficient procedure to treat drop attacks.…”
Section: Vestibular Neurectomymentioning
confidence: 94%
“…House [28] introduced the middle fossa approach. Regardless of the access, the decompression technique had a success rate of up to 90% in the control of vertigo [29][30][31][32][33]. Colletti et al [4] conducted a comparative study on 209 patients who DOI: http://dx.doi.org /10.5772/intechopen.88014 underwent neurectomy, comparing a group of 24 patients who received intratympanic gentamicin (ITG), chemical labyrinthectomy neural ablation therapy.…”
Section: Vestibulocochlear Nerve Neurectomymentioning
confidence: 99%